Implementasi Aplikasi Penunjuk Lokasi Objek Wisata Kota Surabaya Menggunakan Teknologi Augmented Reality - Hendry Gozali; Leo Willyanto Santoso; Rudy Adipranata (Jurnal Infra, 2020)
Tourism is one of the city travel activities where people and their families enjoy the beauty of the tourist sites. With so many tourist locations in various cities specifically the city of Surabaya, it is necessary to develop an application that can help in terms of finding a specific tourist location for the city of Surabaya.In this research, an application was made to utilize AR (Augmented reality) technology using the JavaScript-based Wikitude SDK library as a means of searching tourist attractions, so that users could more easily find tourist locations using a smartphone camera. This application will run on Android devices.